Improvement of methods of comprehensive assessment of the operation efficiency of centralized heat supply systems in municipal heat power engineering - Kozlov, Igor; Kovalchuk, Vyacheslav; Klymchuk, Oleksandr; Sova, Katerina; Aksyonova, Inna; Borysenko, Krystyna (Eastern-European Journal of Enterprise Technologies, 2021)
The possibility of a comprehensive assessment of the efficiency of the operation of a district heating system based on the indicator of the overall efficiency of the equipment OEE (overall equipment efficiency) and its extension to the system as a whole is considered. The disunity of the direction of existing approaches in assessing the efficiency of operation of district heating systems does not allow a comprehensive assessment of the overall efficiency of the functioning of the technological sequence of the entire system. It is proposed to consider efficiency as the probability of full functioning of all elements of the heat supply system. It is shown that the heat output of the boiler house is proportional to the power consumption of the boiler house and is approximated by a periodic function. It is shown that the main element of the heat supply system, which determines its efficiency, is the heat-generating source. As a result of the study, it is determined that the efficiency of the heat-generating source functioning increases as the maximum value of its efficiency is reached. Numerical modeling has shown that the flexible use of the installed heat generator capacity contributes to an increase in the efficiency factor from 0.53 to 0.70 and the overall efficiency of the heat supply system can be increased by more than 30 %. When designing a boiler house, it was recommended to provide for the installation of capacities with gradation 1; 0.5; 0.25. It is shown that the OEE indicator allows one to characterize the efficiency of both the heat supply system as a whole and its individual components, and can be used in the design and analysis of the operation of systems